The Limits of the State: Coercion and Consent in Chinese Tibet - Pirie, F (2013)
Although China's Tibetans profoundly mistrust the ideologies of the party-state, associating them with illegitimate practices of domination, protest and revolt are rare and effectively suppressed. This might be seen as quasi-colonial domination, the state securing subjection through the performance of paramount power, demonstrated by its suppression of the 2008 protests, or it could be attributed to a form of indirect rule, by which local officials engage with local leaders to generate hegemonic consent. While both dynamics are present on the Tibetan plateau, ethnographic fieldwork among the Tibetan populations of Qinghai and Gansu Provinces reveals that consent is primarily generated by local officials who negotiate a form of local order with religious and tribal leaders. Ignoring the ideological demands of their superiors, they engage constructively with the expectations of the Tibetans about how order should be maintained and, in doing so, subvert the state's ideal of uniform and unitary sovereignty. © The Association for Asian Studies, Inc., 2013.